The search for meaning - Naylor, Thomas H., 1936-2012.; Willimon, William H.; Naylor, Magdalena R., 1950- (Nashville : Abingdon Press, 1994)
A process that involves coming to grips with what it means to be human.
Includes bibliographical references (p. 217-221).
Keywords: Life; Meaning (Philosophy); Spiritual life